Leadership Values in the Life of Traditional and Modern Society: An Historical Study - Wahyudin, Yusuf (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: Leadership values are values associated with the actions conducted by a leader. In terms of leadership behavior, there are âessential valuesâ or values of faith, kindness, intelligence, proficiency, and so on, in which a leader must naturally have. In addition to the âessential valuesâ sourced from religious teaching, there are also essential values sourced from local wisdom. However, leadership values have undergone transformations with time. It is inseparable from the growth of the advanced civilization that causes the leadership values rooted from religious teaching and local wisdom to shift to leadership values rooted from worldly teaching. In other words, all of the leadership values rooted from religious teaching and local wisdom will eventually erode and shift to processed value. This scientific article analyzes leadership phenomenon occurring in the life of a society. In general, society leadership values have shifted with time. It is inseparable from the growth of the advanced and developing civilization, of which the results affect all aspects of life, including leadership. The article describes several models of leadership values prevailing in traditional, modern, and post-modern society, which in fact has dynamically moved. In order to understand it, descriptive study with library research method is used. Meanwhile, the study aims to reveal the changes in leadership models existing in traditional, modern, and post-modern society to allow the result of this study to be used as a learning tool for public.KEY WORDS: Leadership values, essential values, religious teaching, local wisdom, traditional, modern, and post-modern societies, and learning tool for public.About the Author: Yusuf Wahyudin, M.M.Pd. is an Educator and a Principal at the SDN (Sekolah Dasar Negeri or Public Elementary School) Banjarsari, Jalan Merdeka No.22 Bandung, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: tsaryusuf@gmail.comHow to cite this article? Wahyudin, Yusuf. (2015). âLeadership Values in the Life of Traditional and Modern Society: An Historical Studyâ in TAWARIKH: International Journal for Historical Studies, Vol.7(1) October, pp.121-130. Bandung, Indonesia: Minda Masagi Press, ISSN 2085-0980.Chronicle of the article: Accepted (May 7, 2015); Revised (August 17, 2015); and Published (October 28, 2015).